DETEKSI KERAGAMAN SPESIES BAKTERI METANOGEN RUMEN SAPI MENGGUNAKAN KLONING GEN 16S rRNA DAN SEKUENSING - Shoffiana Noor; Hendro Pramono; Saefuddin Aziz (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Ruminants produce methane gas which contributes to enhanced greenhouse effect in the atmosphere. Cattle issued the highest methane during the fermentation of feed in the rumen. Methane gas produced by methanogen bacteria in carbohydrates anaerobic fermentation. Methanogen bacteria are difficult to obtain diversity information because difficult cultured. One technique can be used is molecular rRNA 16S gene cloning and sequencing. This study was aims to determine the species diversity of methanogen bacteria in cattle's rumen using rRNA 16S gene cloning and sequencing technique by survey method. The results obtained 51 clones with 800 bp insert size length. The sequencing resulted 2 different sequences, ie 8-3L21 clone bacterium uncultured and BBS-12 clone methanogens rumen uncultured rRNA 16S gene partial sequence with 99% and 100% similarity. The Genus sequences for gene 1 and 3 were Prevotella (24%), Clostridium (1.5%), and other uncultured bacteria, whereas the 2 gene sequences of species was Methanobrevibacter ruminantium (21.83%), M. millerae (29.17%), M. gottschalkii (6.47%), Methanosphaera stadtmanae, and Methanobacterium alcaliphilum. This research provides scientific information about cattle rumen methanogen bacteria species diversity which can be used as a basis for control of cattle rumen methanogen bacteria.